The Relationship between Resiliency and Quality of Life in Senior Undergraduate Students in Private University - Verawati Verawati; Karina Megasari Winahyu; Fauzan Hakim; Eriyono Budi Wijoyo (Ruang Ide, 2022)
Background: The COVID-19 pandemic significant impact on people worldwide, both on the health system and social life, particularly on education. This study aimed to identify the relationship between resilience and quality of life in senior undergraduate students at the Universitas Muhammadiyah Tangerang during the COVID-19 pandemic. Methods: The study used descriptive with a cross-sectional approach. Data collection using WHOQOL-BREF and CD-RISC questionnaires have been tested for validity and reliability. The sample was 100 respondents who were taken by stratified nonrandom sampling. Data were analyzed using Pearson correlation. Results: The results revealed there is a positive and strong correlation between resiliency and quality of life. Conclusion: Senior undergraduate students who perceived better resiliency are more likely to report a higher quality of life. It suggests that senior undergraduate students need to maintain their resilience to perceive more satisfaction in QoL during pandemic COVID-19. Keywords: COVID-19 Pandemic; Resiliency; Quality of Life; Undergraduate Students